2021
DOI: 10.1038/s41419-021-03535-9
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox and bortezomib synergistically inhibits glioblastoma multiforme growth via simultaneously enhancing JNK/p38 MAPK and NF-κB signaling

Abstract: Ciclopirox (CPX) is an antifungal drug that has recently been reported to act as a potential anticancer drug. However, the effects and underlying molecular mechanisms of CPX on glioblastoma multiforme (GBM) remain unknown. Bortezomib (BTZ) is the first proteasome inhibitor-based anticancer drug approved to treat multiple myeloma and mantle cell lymphoma, as BTZ exhibits toxic effects on diverse tumor cells. Herein, we show that CPX displays strong anti-tumorigenic activity on GBM. Mechanistically, CPX inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The GSH redox system plays an important role in cell survival and apoptosis [ 52 , 53 , 54 ], and inhibition of HPGDS was found to result in a downregulation of the GSH levels and a reduction in cellular drug resistance. Considering that the JNK pathway plays an important role in promoting apoptosis in glioma, and a variety of GSTs can regulate the activation of the JNK signaling pathway [ 42 , 55 , 56 ], we speculate that the resistance-promoting function of HPGDS is partly attributable to the inhibition of apoptosis resulting from downregulated activation of the JNK pathway. In this study, inhibition of HPGDS led to significant activation of JNK phosphorylation, and interference with the activation of the JNK pathway reversed the reduction in cell drug resistance caused by inhibition of HPGDS, indicating that HPGDS functions similarly to other GSTs in regulating the activation level of apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The GSH redox system plays an important role in cell survival and apoptosis [ 52 , 53 , 54 ], and inhibition of HPGDS was found to result in a downregulation of the GSH levels and a reduction in cellular drug resistance. Considering that the JNK pathway plays an important role in promoting apoptosis in glioma, and a variety of GSTs can regulate the activation of the JNK signaling pathway [ 42 , 55 , 56 ], we speculate that the resistance-promoting function of HPGDS is partly attributable to the inhibition of apoptosis resulting from downregulated activation of the JNK pathway. In this study, inhibition of HPGDS led to significant activation of JNK phosphorylation, and interference with the activation of the JNK pathway reversed the reduction in cell drug resistance caused by inhibition of HPGDS, indicating that HPGDS functions similarly to other GSTs in regulating the activation level of apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CPX, an antifungal agent off-patent for several decades, was recently found to have remarkable antitumor effects via growth arrest or cell death induction in various cancers [ 8 , 9 , 25 , 40 ]. Here, we demonstrated the role of CPX in regulating proliferation inhibition and autophagic death of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…CPX has been considered a potential antitumor agent due to its therapeutic potential in preclinical models of various cancers. For instance, CPX inhibits tumorigenesis by inducing apoptosis and protective autophagy in multiple cancers, such as colorectal cancer, glioma, and cervical carcinoma [ 7 , 9 , 25 , 41 ]. However, our study showed that CPX triggers autophagic death rather than apoptotic death in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway has been reported to participate in cell proliferation, senescence, and apoptosis [ 48 ]. The other two studies also showed that a high glucose level triggered DNA damage response and dysregulated MAPK via excessive ROS in hyperglycemia, and an unfolded protein response in ER stress could regulate phosphorylation of JNK causing apoptosis [ 5 , 49 ].…”
Section: Discussionmentioning
confidence: 99%